Normalisation of hypoxaemia following successful percutaneous closure of a bidirectional shunting secundum atrial septal defect without pulmonary hypertension in a patient with severe non‐ischaemic cardiomyopathy and refractory ventricular tachycardia. Issue 8 (August 2016) - Anderson, R. D.; Wilson, W.; Morton, J.; Aggarwal, A.
Abstract : Atrial septal defects (ASD) are an uncommon cause of dyspnoea. A high index of suspicion is required, and further investigation should be prompted in patients with unexplained hypoxaemia, particularly those with pulmonary hypertension. Hypoxic ASD without pulmonary hypertension are rare, and only a handful of cases have been published. We present a middle‐aged man with progressive dyspnoea with a successfully closed ASD without pulmonary hypertension caused by elevated right ventricular pressures secondary to an idiopathic cardiomyopathy.